Neuromelanin-sensitive magnetic resonance imaging in disease differentiation for parkinsonism or neurodegenerative disease affecting the basal ganglia. (June 2021) - Matsuura, Keita; Ii, Yuichiro; Maeda, Masayuki; Tabei, Ken-ichi; Satoh, Masayuki; Umino, Maki; Miyashita, Koichi; Ishikawa, Hidehiro; Shindo, Akihiro; Tomimoto, Hidekazu
Abstract: Introduction: Several reports have shown that neuromelanin-sensitive magnetic resonance imaging (NMI) using 3T magnetic resonance imaging is useful for the differential diagnosis of Parkinson's disease (PD), progressive supranuclear palsy (PSP), and other neurological diseases. However, the number of cases in previous studies has been insufficient. We aimed to determine the relationship between NMI and severity of PD and related disorders, and thereby establish the diagnostic utility of NMI for diagnosing neurological diseases. Methods: We enrolled 591 patients (531 subjects after removal of duplicates) with parkinsonism who underwent NMI. The contrast ratio of the locus coeruleus (LC-CR) and the area of the substantia nigra pars compacta (SNc) were analyzed in each patient. Results: The patients' clinical diagnoses were as follows: 11 patients in the disease control group (DCG), 244 patients with PD, 49 patients with PSP, and 19 patients with multiple system atrophy with predominant parkinsonism. Additionally, some patients were diagnosed with dementia with Lewy bodies, vascular parkinsonism, and drug-induced parkinsonism. SNc in the patients with PD and PSP was significantly smaller than that in DCG. LC-CR in the patients with PD was lower than that in DCG; furthermore, LC-CR in the patients with PD was significantly lower than that in the patients with PSP. We found that an area under the receiver-operating characteristic curve, indicating diagnostic efficacy, of 0.85 for LC-CR is a promising biomarker for differentiating PD from PSP. Conclusion: NMI effectively contributes to differentiating neurodegenerative diseases, such as PD and PSP. Highlights: 531 cases of neuromelanin imaging in the disease of Parkinsonism. The contrast of locus coeruleus is useful for discriminating PD and PSP. Neuromelanin imaging can discriminate PD from VaP, DIP and ET. Neuromelanin imaging of PD and DLB resemble.